Corticospinal Pathways and Interactions Underpinning Dexterous Forelimb Movement of the Rodent. (1st December 2020) - Basista, Mark J.; Yoshida, Yutaka
Highlights: The interconnectedness and activity of the neural circuits involved in dexterous movement in the rodent are reviewed. Recent experiments that shed light on the time course of neural activity along the motor control axis are summarized. Task dexterity is proposed as a variable that could reconcile some recent experiments with seemingly contradictory results. The degree of sensory processing in a task is likely a factor in the recruitment of the rodent corticospinal circuits. Abstract: In 2013, Thomas Jessell published a paper with Andrew Miri and Eiman Azim that took on the task of examining corticospinal neuron function during movement (Miri et al., 2013 ). They took the view that a combination of approaches would be able to shed light on corticospinal function, and that this function must be considered in the context of corticospinal connectivity with spinal circuits. In this review, we will highlight recent developments in this area, along with new information regarding inputs and cross-connectivity of the corticospinal circuit with other circuits across the rodent central nervous system. The genetic and viral manipulations available in these animals have led to new insights into descending circuit interaction and function. As species differences exist in the circuitry profile that contributes to dexterous forelimb movements (Lemon, 2008; Yoshida and Isa, 2018 ), highlighting important advances in one model could help to compare and contrast with what is known about other models. We will focus on the circuitry underpinning dexterous forelimb movements, including some recent developments from systems besides the corticospinal tract, to build a more holistic understanding of sensorimotor circuits and their control of voluntary movement. The rodent corticospinal system is thus a central point of reference in this review, but not the only focus.